Hospital Resilience After the 2015 Earthquake in Nepal: Results From Semi-structured Interviews With Hospital Staff - Moitinho de Almeida, Maria; van Loenhout, Joris Adriaan Frank; Singh Thapa, Sunil; Kumar, K. C.; Prakash Mahara, Deepak; Guha-Sapir, Debarati; Aujoulat, Isabelle (Frontiers in Public Health, 2021)
Background: Resilient hospitals are increasingly recognized as a cornerstone of disaster reduction in global policies such as the Sendai Framework for Action. However, current hospital resilience frameworks emerged from pre-disaster conceptualizations, and have not been verified in real-life disaster contexts nor in the frontlines. Our aim was to study a tertiary hospital's resilience after the 2015 earthquake in Nepal, as experienced by its staff. Methods: We undertook a qualitative study in the Tribhuvan University Teaching Hospital (TUTH), where we conducted 18 semi-structured interviews with hospital staff. We inductively created themes to describe the earthquake burden to the hospital, and to analyze individual resilience of hospital staff. In addition, we deductively documented the resilience of the hospital as a system, according to the system resilience dimensions: means of resilience (redundancy and resourcefulness), and ends of resilience (robustness and rapidity). Results: In terms of robustness, TUTH increased its capacity for earthquake victims as elective activities were temporarily interrupted and quality of care was not a priority. Three stages of rapidity were identified: critical rapidity to address immediate needs, stabilizing rapidity until the hospital re-started routine activities, and recovery rapidity. In addition to the disaster plan, emerging adaptations played a major role in redundancy and resourcefulness. We found that individual resilience depended on three determinants: safety, meaningfulness, and sense of belonging. Conclusions: Hospital resilience results from a complexity of emerging and planned adaptations, as well as from interdependencies with individual resilience. Frameworks and plans to improve hospital resilience must reflect flexibility of response, and a concern for well-being of hospital staff is central for sustainable disaster response and improved resilience.